Nanoporous metals by alloy corrosion: Bioanalytical and biomedical applications. (10th January 2018) - Şeker, Erkin; Shih, Wei-Chuan; Stine, Keith J.
Abstract: Abstract : Nanoporous metals obtained by dealloying have attracted significant attention for their unusual catalytic properties, and as model materials for fundamental studies of structure–property relationships in a variety of research areas. There has been a recent surge in the use of these metals for biomedical and bioanalytical applications, where many exciting opportunities exist. The goal of this article is to provide a review of recent progress in using nanoporous metals for biological applications, including as biosensors for detecting biomarkers of disease and multifunctional neural interfaces for monitoring and modulating the activity of neural tissue. The article emphasizes the unique properties of nanoporous gold and concludes by discussing its utility in addressing important challenges in biomedical devices.